Metody pomiaru ryzyka rynkowego w systemie controllingu - Kaszuba-Perz, Adrianna; Perz, Paweł (Methods of measuring financial risk in the system of controlling, 2008)
Information about company's exposition on market risk is fundamental in managerial decisions. Procedure of measuring risk based on Value at Risk methodology is presented in the paper. The Value at Risk method is popular within financial institutions, we think that similar methods (EaR, CFaR, EPSaR) may be successfully implemented in companies. Risk measurement based on such methods gives management valuable and coherent information and enables to introduce effective risk management system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 133-140